Insulin pretreatment during mid-cycle and programmed breeding on conception ofrepeat breeding crossbred cows - Jayaganthan, Ponnusamy; Satheshkumar, Soundarapandian; Krishnakumar, Karuppasamy; Murugavel, Sokkalingam; Jagadeesan , Krishnan (The Indian Journal of Animal Reproduction, 2024)
The effect of insulin (Ins) pretreatment during mid-cycle on conception rate of repeat breeding (RB) cows subjected for programmed breeding was studied. A total of 74 RB crossbred cows which were found to be free of SCE were randomly divided into two groups. Group I (Control; n=12): Animals were inseminated on oestrus (Day 0) without any treatment. Group II – (INS; n = 12): RB cows were administered with Biphasic Insulin product (0.25units /kg BW s.c.) for three days from Day 8 to Day 10 of the cycle (Day 0 – oestrus). Prostaglandin (PG) (Cloprostenol: 500 mcg, i.m.) was administered on Day 11. On the day of induced oestrus (Day 0i) i.e., 48 h post PG, all the 12 cows were inseminated with GnRH (n=6) and GnRH + Ins (n=6). Blood samples were collected on Day 0 and 10 in both groups and on the day of induced oestrus (Day 0i) in INS group for Insulin estimation. Ins concentration was significantly (P < 0.05) increased in INS group on Day 10 and Day 0i in response to Ins treatment. In control group, the conception rate among the RB cows was found to be 34.00 per cent. A significantly (P < 0.01) high conception rate (66.67%) was recorded in the INS group among RB cows, when inseminated with or without INS during the induced oestrus, than the Control group. It could be concluded that INS therapy during the mid-cycle prior to PG induced programmed breeding can improve the conception rate in RB cows.